The future of private sector unions in the U.S. - Lipset, Seymour Martin; Katchanovski, Ivan (Journal of Labor Research)
Part of a special issue on the future of private sector unions in the U.S. The writers examine the reasons for the decline in union density that has marked the U.S. union movement since the 1950s. The data are based largely on an Angus Reid polling organization survey in 1996, which focuses on membership and attitudes toward unions in the U.S.